STRATEGIES FOR IMPROVING NON-ACADEMIC ACHIEVEMENT OF ELEMENTARY SCHOOL STUDENTS WITH LOW SOCIOECONOMIC STATUS - Awalliyah, Rinda Ayu Nur; Abduh, Muhammmad (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2025)
This study aims to describe the factors that cause low-economic elementary schools to have excellence in the non-academic field, as well as to describe the strategies applied by teachers with students who have excellence in the non-academic field. The method used in this research is a type of case study research with a qualitative approach, data collection techniques are carried out by interview, observation, and documentation. The results in this study are 1) The factors underlying the excellence of the non-academic field at MIM Pucangan are: Utilization of funds properly, giving awards and support as motivation, student habituation, and collaboration of supportive schools. 2) The strategy carried out by teachers in improving the excellence of the non-academic field is to improve the quality of mentors and make good use of infrastructure.